MENINGKATKAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI TEKNIK USAP ABUR MENGGUNAKAN MEDIA KRAYON DI TAMAN KANAK-KANAK NEGERI 15 MENDALO DARAT KECAMATAN JAMBI LUAR KOTA KABUPATEN MUARO JAMBI - Indah Nuraini; Fiqi Nurmanda Sari; Anisa (STKIP Subang, 2026)
This study aims to improve the fine motor skills of children aged 5–6 years through the application of the rubbing technique using crayon media at State Kindergarten 15 Mendalo Darat. The problem identified in this research is that children's fine motor development is still not optimal, particularly in eye-hand coordination and finger control. This research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart spiral model, consisting of planning, action, observation, and reflection stages. The subjects of this study were 14 children in group B. Data collection techniques included observation, interviews, and documentation. The findings showed a significant improvement in children’s fine motor skills in each cycle. In the pre-cycle, the average achievement was 35% (Starting to Develop). It increased to 59% (Developing as Expected) in Cycle I, and reached 97% (Very Well Developed) in Cycle II. These results indicate that the rubbing technique using crayon media is highly effective in enhancing children’s fine motor skills. This technique not only strengthens small muscle coordination but also provides a creative and enjoyable learning experience for children